Treasured bodies : an examination of the W.G. De Haas anatomy study resource's pathology collection, technical aspects, and perspectives for conservation - Loubser, Maggi (University of Pretoria, 2024)
Mini Dissertation (MSocSci (Heritage and Cultural Sciences))--University of Pretoria, 2023.